Active decisions and pro-social behavior: a field experiment on blood donation - Alois Stutzer; Lorenz Goette; Michael Zehnder (Institute for the Study of Labor (IZA), 2006)
In this paper, we propose a decision framework where people are individually asked to either actively consent or dissent to some pro-social behavior. We hypothesize that confronting individuals with the choice of engaging in a specific pro-social behavior contributes to the formation of issue-specific altruistic preferences while simultaneously involving a commitment. The hypothesis is tested in a large-scale field experiment on blood donation. We find that this active-decision intervention substantially increases the stated willingness to donate blood, as well as the actual donation behavior of people who have not fully formed preferences beforehand.
Keywords: C93; D64; I18; 330; active decision; pro-social behavior; field experiment; blood donation; Altruismus; Test